Alteration in Intracellular Zn2+ Homeostasis as a Result of TRPM2 Channel Activation Contributes to ROS-Induced Hippocampal Neuronal Death - Li, Xin; Yang, Wei; Jiang, Lin-Hua (Frontiers in Molecular Neuroscience, 2017)
Transient receptor potential melastatin-related 2 (TRPM2) channel, a molecular sensor for reactive oxygen species (ROS), plays an important role in cognitive dysfunction associated with post-ischemia brain damage thought to result from ROS-induced TRPM2-dependent neuronal death during reperfusion. Emerging evidence further suggests that an alteration in the Zn2+ homeostasis is critical in ROS-induced TRPM2-dependent neuronal death. Here we applied genetic and pharmacological interventions to define the role of TRPM2 channel in ROS-induced neuronal death and explore the mechanisms contributing in the alteration in intracellular Zn2+ homeostasis in mouse hippocampal neurons. Exposure of neurons to 30-300 M H2O2 for 2-24 hr caused concentration/duration-dependent neuronal death, which was significantly suppressed, but not completely prevented, by TRPM2-knockout (TRPM2-KO) and pharmacological inhibition of the TRPM2 channel. H2O2-induced neuronal death was also attenuated by treatment with TPEN acting as a Zn2+ selective chelator. Single cell imaging demonstrated that H2O2 evoked a prominent increase in the intracellular Zn2+ concentration, which was completely prevented by TPEN as well as TRPM2-KO and inhibition of the TRPM2 channel. Furthermore, H2O2 induced lysosomal Zn2+ release and lysosomal dysfunction, and subsequent mitochondrial Zn2+ accumulation that provokes mitochondrial dysfunction and ROS generation. These H2O2-induced lysosomal/mitochondrial effects were prevented by TRPM2-KO or TPEN. Taken together, our results provide evidence to show that a dynamic alteration in the intracellular Zn2+ homeostasis as a result of activation of the TRPM2 channel contributes to ROS-induced hippocampal neuronal death.